STIGMA DAN PROSES SOSIALISASI WARIA SERTA DAMPAKNYA PADA PENINGKATAN RISIKO PENULARAN IMS DAN HIV/AIDS - Gani, Husni Abdul; Rokhmah, Dewi (FKM - UNEJ, 2011)
Being a transvestitesÂ is assumedÂ as deviate behaviour by our society. It is severed with negative stigmatizationÂ as badÂ Â Â image, dirty, criminal, and havingÂ deviateÂ sexual orientation, cause this group of people have more risky toward psychological and sexual impact in transmision of STDÂ Â Â and HIV/AIDS. Sosialization proces is needed by transvestitesgeting acceptance in social environment, because transvestitesÂ could not separate from social context. This study aims to analyze the stigmatizationÂ and sosialization process toward transvestites and its impact for the increasing of transmission risk fromÂ Â STD and HIV/AIDS.It was a qualitative study involved informants aged 25-54Â with purposive samplingÂ in Semarang city. DataÂ was collected by indepht interview and theyâre analyzed by thematic content analysis. The result of this study showed that stigmatization to transvestites was derived from publicÂ society and religius community.Â ThisÂ rejectionÂ impacts at sosializationÂ Â Â process in family, work placeÂ and society.Â BecauseÂ our societyÂ assume transvestites identical with deviate behaviour from the norm, and having tranvestites as the family member means ignominy. Consequently they choose as a urbant people.Â It cause the increasing of transmission risk on STD and HIV/AIDS.Â There are no obstacle in sosialization process with other transvestitesÂ in cebongan. Cebongan is the place they can express themself without rejection fromÂ Â others. So they can be received as normal individual.Â Society is expected acceptingÂ them as a part of their live, with involved them include transvestites with HIV/AIDS in society activity.Key words : Transvestites, stigmatization, sosialization process, STD and HIV/AIDS